We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
159
1
avatar+397 

deleted.

 Jun 12, 2019
edited by sinclairdragon428  Nov 20, 2019
 #1
avatar+105462 
+1

\( \frac{1-n}{n+1} + \frac{n-1}{1-n} = 1\)

 

(1-n)^2 + (n+ 1)(n - 1)

_________________     =      1                  multiply both sides by the fraction denominator

      (1 + n) (1 - n)

 

(1 - n)^2 + (n+ 1) (n - 1)    =  (1 + n) (1 - n)     simplify

 

1 - 2n + n^2 + n^2 - 1  =   1 - n^2

 

2n^2  - 2n = 1 - n^2

 

3n^2 - 2n - 1  = 0

 

(3n + 1) (n - 1) = 0

 

Set each factor to 0 and solve for n

 

3n +1 = 0                n - 1   = 0

3n = -1                    n = 1      (reject as this makes an original denominator = 0 )

n = -1/3

 

 

 

cool cool cool

 Jun 12, 2019

25 Online Users

avatar